Emergency at the Borders: Response to Refugees in Sallum Camp - Hassanein, Shaimaa HY (AUC Knowledge Fountain, 2026)
This thesis examines the emergency humanitarian response at Sallum camp at the Egyptian border upon the Lybian crisis between 2011 and 2014. By positioning the lived experiences and perspectives of humanitarian aid workers at the center, this research argues that the camp constituted a distinct and dynamic space shaped by shifting geopolitical conditions, state sovereignty concerns, and bureaucratic ambiguity. Drawing on qualitative interviews with frontline humanitarian aid workers who operated and lived in the camp over extended periods, the study explores how humanitarian interventions were negotiated, adapted, and implemented within a highly constrained environment. The thesis highlights the Egyptian state’s stance to the emergency camp, coupled with securitization measures and evolving administrative controls, produced a liminal space where displaced populations remained physically and legally suspended between entry and exclusion. Within this context, humanitarian operations were not merely technical responses but processes deeply interconnected with state power and governance. By focusing on the everyday practices of humanitarian workers, the research reveals how these actors navigated competing institutional mandates, improvised in response to rapidly changing conditions, and played a pivotal role in mediating between displaced populations and state authorities. Ultimately, the thesis contributes to debates on humanitarianism by demonstrating how frontline actors actively shape, reproduce, at times contest structures and create informal structures of control and management emergency settings.